Contesting Christendom Readings in Medieval Religion and Culture. - Halverson, James L. (Lanham : Rowman & Littlefield Publishers, 2007)
This reader fills a gap in classroom offerings by exploring historians' ongoing attempt to understand the social and cultural aspects of medieval Christianity. James L. Halverson organizes his selections around two central questions: what do we mean when we say that medieval Europe was a Christian culture, and what did it mean to be a Christian in the Middle Ages? He argues that the diversity of medieval society over time and space defies the simple answers given in textbooks and that students of medieval religion must have more exposure to issues such as class, gender, and literacy. This care.
Chapter 19 The Stripping of the Altars: Traditional Religion in England, ca. 1400-1580 Eamon DuffyChapter 20 Religion and the Decline of Magic Keith Thomas; Chapter 21 Women in the Late Medieval English Parish Katherine L. French; Chapter 22 The Magnificent Ride: The First Reformation in Hussite Bohemia Thomas A. Fudge; Index; About the Editor; About the Contributors.
Print version record.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Master record variable field(s) change: 650
Keywords: Church history -- Middle Ages, 600-1500.; Civilization, Medieval; Christianity and culture; Christianity and culture; Church history -- Middle Ages, 600-1500.; Civilization, Medieval; RELIGION -- Christian Church -- History; RELIGION -- Christianity -- History; Christianity and culture; Church history -- Middle Ages; Civilization, Medieval; 600-1500; Electronic books